2014
DOI: 10.1124/dmd.114.061424
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extrahepatic Metabolism in the Pharmacokinetics of the Targeted Covalent Inhibitors Afatinib, Ibrutinib, and Neratinib

Abstract: Despite the fact that much progress has been made recently in the development of targeted covalent inhibitors (TCIs), their pharmacokinetics (PK) have not been well characterized in the light of extrahepatic clearance (CL extH ) by glutathione (GSH)/glutathione S-transferase (GST)-dependent conjugation attributable to the unique electrophilic structure (e.g., acrylamide moiety) of TCI compounds. In the present study, CL extH values were examined in rat, dog, and monkey to predict the contribution of CL extH to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 41 publications
4
71
0
3
Order By: Relevance
“…Shibata and Chiba have investigated the correlation between clearance predicted from hepatocyte incubations and total body clearance for three covalent binding TKIs (afatinib, ibrutinib, and neratinib). The authors noted a disconnect between in vivo and in vitro clearance attributed to extrahepatic (covalent) conjugation to glutathione not captured in the hepatocyte system (Shibata and Chiba, 2015). For osimertinib, the in vitro studies indicated that direct conjugation with glutathione would be a minor metabolic pathway in humans; however, it is clear from the human ADME study that a high proportion of [ 14 C]-osimertinib-related material is excreted bound to proteinaceous material contributing a substantial fraction of overall clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Shibata and Chiba have investigated the correlation between clearance predicted from hepatocyte incubations and total body clearance for three covalent binding TKIs (afatinib, ibrutinib, and neratinib). The authors noted a disconnect between in vivo and in vitro clearance attributed to extrahepatic (covalent) conjugation to glutathione not captured in the hepatocyte system (Shibata and Chiba, 2015). For osimertinib, the in vitro studies indicated that direct conjugation with glutathione would be a minor metabolic pathway in humans; however, it is clear from the human ADME study that a high proportion of [ 14 C]-osimertinib-related material is excreted bound to proteinaceous material contributing a substantial fraction of overall clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Neratinib also retains electrophilic reactivity to the Cys residue of glutathione (GSH) by forming a GSH adduct 28. We investigated the chemical reactivity of neratinib with GSH (Figure S31).…”
mentioning
confidence: 99%
“…Even though all of these acrylamides were electrophilic and prone to Michael addition with small molecule thiols such as glutathione and cysteine (data not shown), HSA posed a different challenge as it has several lipophilic binding pockets. Many kinase inhibitors, including the ones investigated, have been shown to have high plasma protein binding affinities and we postulated that the level of conjugation of HSA by afatinib and canertinib was due to non‐covalent HSA binding, thereby lowering the free concentration of the small molecule drug available to conjugate to the surface exposed thiol . Due to the low conjugation profiles of PD‐168393, afatinib and canertinib, MS e CID fragmentation did not produce detectable unique fragment ions and further investigation with these compounds was halted.…”
Section: Resultsmentioning
confidence: 99%